In patients with osteoporosis, should subclinical hyperthyroidism be treated?. Issue 4 (April 2017) - Adam, Patricia; Tsvilina, Alexandra
Abstract : EVIDENCE‐BASED ANSWER : Subclinical hyperthyroidism with thyroid‐secreting hormone (TSH) ≤0.45 mIU/L is associated with an increased fracture rate (SOR: A, meta‐analysis of cohort studies), but treatment of subclinical hyperthyroidism when TSH is ≤0.2 mIU/L only slightly increases bone mineral density (BMD) (SOR: C, case‐control study with disease‐oriented outcomes). Current guidelines recommend clinicians "strongly consider" treatment of subclinical hyperthyroidism in patients with osteoporosis and TSH persistently <0.1 mIU/L (SOR: C, expert opinion).